2016
DOI: 10.1371/journal.pone.0146530
|View full text |Cite
|
Sign up to set email alerts
|

Largescale Transcriptomics Analysis Suggests Over-Expression of BGH3, MMP9 and PDIA3 in Oral Squamous Cell Carcinoma

Abstract: Oral squamous cell carcinoma (OSCC) has been reported as the most prevalent cancer of the head and neck region, while early diagnosis remains challenging. Here we took a comprehensive bioinformatics study on microarray data of 326 OSCC clinical samples with control of 165 normal tissues. The cell interaction pathways of ECM-receptor interaction and focal adhesion were found to be significantly regulated in OSCC samples. Further analysis of the topological properties and expression consistency identified that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 50 publications
5
25
0
Order By: Relevance
“…The contribution of upregulated Wnt/β-catenin signalling to cell survival and invasion in HNSCC has been previously discussed [15], [25], [26]. Recent work suggests that transcriptional regulation of focal adhesion genes plays a crucial role in OSCC pathogenesis and that focal adhesion kinase ( FAK ) is a key mediator of extracellular matrix interactions and cellular signalling, contributing to HNSCC onset and progression [27], [28].…”
Section: Resultsmentioning
confidence: 99%
“…The contribution of upregulated Wnt/β-catenin signalling to cell survival and invasion in HNSCC has been previously discussed [15], [25], [26]. Recent work suggests that transcriptional regulation of focal adhesion genes plays a crucial role in OSCC pathogenesis and that focal adhesion kinase ( FAK ) is a key mediator of extracellular matrix interactions and cellular signalling, contributing to HNSCC onset and progression [27], [28].…”
Section: Resultsmentioning
confidence: 99%
“…MMPs, a group of zinc‐dependent endopeptidases, can degrade various components of the extracellular matrix and the basement membrane and is associated with tumor progression . MMP‐2 and MMP‐9 over‐activation are linked to poor survival in OSCC cases . EGCG, the most well‐known polyphenol in tea, inhibits the migration of human uveal melanoma cells by inhibiting MMP‐2 .…”
Section: Discussionmentioning
confidence: 99%
“…MMP‐2 and MMP‐9 have been associated with metastasis and invasion in human OSCCs . A recent study has demonstrated that MMP‐9 is significantly overexpressed in OSCCs compared to normal tissue and that protein expression increased from normal mucosa to oral leukoplakia to OSCC .…”
Section: Cellular Responses To Hypoxiamentioning
confidence: 99%